2013
DOI: 10.1097/aog.0b013e31829d5a33
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Compared With Therapeutic Ibuprofen Analgesia in First-Trimester Medical Abortion

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 14 publications
0
44
1
1
Order By: Relevance
“…Notwithstanding, the high level of pain reported on the visual analog scale and the relatively high proportion of women who reported pain being greater than they expected indicates that there may be room for improved pain management. There is little consensus about the most efficacious pain relief regimen for first‐trimester medical abortion and research is continuing to inform service delivery practice on pain management [13].…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, the high level of pain reported on the visual analog scale and the relatively high proportion of women who reported pain being greater than they expected indicates that there may be room for improved pain management. There is little consensus about the most efficacious pain relief regimen for first‐trimester medical abortion and research is continuing to inform service delivery practice on pain management [13].…”
Section: Discussionmentioning
confidence: 99%
“…The woman should be sent home with appropriate instructions for analgesia with over-the-counter medications and can be provided with prescriptions for oral narcotics to use when needed. One randomized trial found that multiple doses of ibuprofen given prophylactically at the time of misoprostol administration did not significantly reduce pain associated with medical abortion compared with ibuprofen taken when needed (51). One randomized trial found that ibuprofen taken when needed was more effective than acetaminophen to reduce pain associated with medical abortion (49).…”
Section: Medical Abortion Versus Surgical Abortionmentioning
confidence: 99%
“…18 Several studies have 41 Medical Abortion for Clinical Practice & CME Review Article evaluated first-trimester medical abortion beyond 63 days' gestation. Three studies done in Europe found high success rates, but for each of these, the women were hospitalized for the abortion procedure.…”
Section: Gestational Age Limitsmentioning
confidence: 99%
“…A recent study of 250 women undergoing medical abortion did not show any benefit to taking ibuprofen before the onset of pain from medical abortion, as opposed to taking it after the onset of pain. 41 Although commonly prescribed, and apparently needed by most women undergoing medical abortion, no studies have evaluated opioid analgesics agents in comparison to ibuprofen to determine their efficacy for pain relief.…”
Section: Troubleshootingmentioning
confidence: 99%